Identification of cleavage regulatory mechanisms and phenotypic consequences to targeting of the ADAM 17/ EGFR axis in triple negative breast cancer (TNBC) in-vitro - Bagchi, Udita (2015)
Ectodomain cleavage of cel l-surface proteins by A Disintegrin And\nMetalloproteinases (ADAMs) is highly regulated, and its dysregulation has\nbeen l inked to many diseases. ADAM17-dependent Epidermal Growth Factor\n(EGF) pro-ligand cleavage drives mammary carcinogenesis, proliferation,\nmigration and invasion of Triple Negative Breast Cancer (TNBC) cells\nboth in vitro and in vivo. ADAM 17 over-expression in TNBC patients\nnegatively predicts adverse outcomes in breast cancer patients and has\nrecently been suggested as a novel diagnostic tool and therapeutic target.\nThis thesis explores the potential to understand shedding regulation\nupstream of ADAM17 for ADAM17/EGFR ligand axis targeting in TNBC. The\noverall objective is to investigate the cleavage of ADAM17 substrates by\nexamining the effect of enzyme inhibitors targeting different signal ing\nmolecules (kinases, phosphatases and cytoskeletal components) on basal\nand phorbol ester-induced ADAM17-mediated substrate cleavage and EGFR\nphosphorylation in MDA-MB-231cells.\nADAM17 cleavage regulators have been identified as new drug targets in\nTNBC. In line with this objective, the role of two recently identified ADAM17\ndependent cleavage regulators from the lab, Protein Kinase C alpha (PKC-?)\nand Protein Phosphatase 1 Regulatory (inhibitor) subunit 14 (PPP1R14D), in\nTNBC relevant cellular responses have been evaluated. Firstly, inducible\nknockdown (KD) of these targets was achieved in the TNBC epi thelial cel l\nline MDA-MB-231 via lentiviral IPTG-inducible shRNA vector system (pLKO-\n904) and i ts effects on migration, invasion and cell proliferation was tested\nin vitro. These in vitro results were correlated with in vivo results obtained\nby transplanting the same cel ls via orthoptopic mammary fat-pad\ntransplantation into mice.\nFor both approaches, Western blot analysis of total protein extracts isolated\nfrom whole cell lysates was used to determine the phosphorylated and total\nlevels of Epidermal Growth Factor Receptor (EGFR) as wel l as of its\ndownstream targets Extracel lular signal-Regulated Kinases (ERKs), Protein\nKinase B (PKB/Akt) and Signal Transducer and Activator of Transcription 3\n(STAT3). qPCR was used to study the expression levels of EGFR and of\nother Receptor Tyrosine Kinases (RTKs). ELISAs using cell culture\nsupernatants were conducted to measure cleaved ADAM17 substrates such\nas soluble transforming-growth-factor-alpha (TGF-?), heparin-binding EGF\n(HB-EGF), amphiregul in, tumor-necrosis-factor-receptor-1 (TNFR1) along\nwith the ADAM10 substrate R/c Met.\nWe found that the shedding regulation occurs on the substrate level and that\nProtein Kinase C (PKC) activity is essential in the regulation of EGF l igand\ncleavage. PKC? and PPP1R14D knockdown resul ted in significantly reduced\nmigration, invasion and cellular proliferation of cells, suggesting that\ntargeting of PKC? and PPP1R14D could provide a therapeutic benefit in\nTNBC. Targeting cleavage regulators that address substrates instead of the\nprotease could prevent the observed negative side effects of broadspectrum\nmetal loprotease inhibitors in patients, which were due to nonselective\nsubstrate cleavage inhibition. Since single targeted therapies, in\nparticular therapies directed against the EGFR, often induce resistance,\nEGF l igand cleavage regulator targeting could be used in combination with\ndirect EGFR targeting for better therapeutic benefit.